Influence of water to binder ratio on the rheology and structural Build-up of Alkali-Activated Slag/Fly ash mixtures. (20th December 2020) - Dai, Xiaodi; Aydin, Serdar; Yardimci, Mert Yücel; Lesage, Karel; de Schutter, Geert
Highlights: Fresh state properties of hybrid AAC with different w/b ratio were investigated. GGBFS provided the main contribution to the increase of storage modulus. The dynamic yield stress, plastic viscosity and thixotropic index decrease with an increase in w/b. The setting times of AAC mixtures are less dependent on the w/b ratio as compared to OPC. Abstract: In this study, the effects of water to binder (w/b) ratio on the rheological and fresh state properties of alkali-activated cement (AAC) pastes have been investigated. A mixture of 50% type F fly ash (FA) and 50% ground granulated blast furnace slag (GGBFS) was activated by a mixture of sodium hydroxide and sodium silicate, in three different w/b ratios of 0.32, 0.37 and 0.42. Setting time, ultrasonic pulse velocity (UPV), heat evolution by isothermal calorimetry, flow spread by mini-slump test, rheological properties by means of flow curve and viscoelastic properties such as storage modulus (G') and loss factor (G'') were determined on the paste mixtures. The results showed that the higher w/b ratio led to structural build-up with higher rate compared to lower w/b ratios. GGBFS provided the main contribution to the increase of storage modulus in the early stage of hybrid mixture of GGBFS and FA. The dynamic yield stress, plastic viscosity and thixotropic index values decrease with an increase in w/b ratio of AAC mixture. The setting times of AAC mixtures were found to be less dependent on the w/b ratio as compared to ordinary Portland cement mixtures.